War and Environment - Smith, Jason W. (The Routledge History of Global War and Society, 2018)
Scholars have offered at least four distinct but interrelated conceptual frameworks for examining the relationship between militaries and the natural world.
Keywords: dept.his

To Master the Boundless Sea: The U.s. Navy, the Marine Environment, and the Cartography of Empire - Smith, Jason W. (University of North Carolina Press, 2018)
"As the United States grew into an empire in the late nineteenth century, notions like 'sea power' derived not only from fleets, bases, and decisive battles, but also from a scientific effort to understand and master the ocean environment. Beginning in the early nineteenth century and concluding in the first years of the twentieth, Jason W. Smith tells the story of the rise of the U.S. Navy and the emergence of American ocean empire through its struggle to control nature. In vividly told sketches of exploration, naval officers, war, and, most significantly, the ocean environment, Smith draws together insights from environmental, maritime, military, and naval history, and the history of science and cartography, placing the U.S. Navy's scientific efforts within a broader cultural context"–
SCSU Faculty Scholar Award
Keywords: History; Naval; History; Cartography; Imperialism and science; United States; History; Nautical charts; SCSU Faculty Scholar Award; United States; United States. Navy; award_winner; dept.his; faculty_collection

Matthew Fontaine Maury: Pathfinder - Smith, Jason W (International Journal of Maritime History, 2016)
Historians have long recognized Matthew Fontaine Maury as an important if controversial figure in the histories of science and of maritime and naval affairs. These assessments, however, rest on scholarship that is by now more than a half-century old. It is therefore appropriate to look at Maury’s significance from fresh perspectives, incorporating recent historiographical trends in the history of science and cartography, environmental history, cultural history and military history. This article focuses on the ways in which Maury’s cartographic work reframed mariners’ understanding of the marine environment away from what he perceived to be a watery wilderness towards an ordered environment safe and favourable to American commerce. Maury was long known as ‘The Pathfinder of the Seas’, but I argue that his significance, in fact, lies in the ways he and his staff at the Naval Observatory organized the sea as a ‘common highway’, tracing paths, but also imposing narratives and constructing new meanings. Maury’s tool was the nautical chart and, particularly, his Wind and Current Charts series that by the 1850s reimagined the ways mariners, navigators and naval officers understood and harnessed the ocean environment. The article briefly considers these charts from three perspectives – method, process and representation – in order to see the ways in which Maury was pushing the boundaries of the cartographic medium to usher in revolutionary ways of envisioning the ocean environment. By quantifying winds, symbolizing whales and infusing the sea with ship tracks, among other things, Maury was imposing potent, if sometimes flawed, new ways of understanding and imagining the sea that were central to American maritime expansion in the antebellum era. In this and other ways, we can see Maury anew, a figure central to the growth of American commercial empire and to new ways of understanding and thinking about the sea.
Keywords: dept.his